Carbon stars in lmc clusters revisited - Marigo, Paola (1996)
Examining the available data for AGB stars in the Large Magellanic Cloud (LMC) clusters, we address the question about the mass interval of low- and intermediate-mass stars which eventually evolve into carbon stars (C stars) during the TP-AGB phase. We combine the data compiled by Frogel, Mould & Blanco (1990) - near infrared photometry and spectral classification for luminous AGB stars in clusters - with the ages for individual clusters derived from independent methods. The resulting distribution of C stars in the Mbol - log(age) plane evidences that the upper and the lower limits of the mass range for the formation of C stars cannot be derived from cluster data. The explanation of this resides in the presence of two different periods of quiescence in the cluster formation history of the LMC, shaping the age (and progenitor mass) distribution of C stars. The most recent of these quiescence episodes could also explain the lack of very luminous AGB stars (with –6 > Mbol > –7) in the clusters, contrary to what observed in the field. Finally we compare the distribution of C stars in the Mbol –log( age) diagram with synthetic models of AGB evolution which were previously constrained to reproduce the observed luminosity function of C stars in the field. These models provide a good description of the relative frequency of M-versus C-type stars.